2014
DOI: 10.1007/s13277-014-2700-8
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of circulating microRNAs as biomarkers for breast cancer: a meta-analysis study

Abstract: Recent studies have provided new insights into the diagnostic value of circulating microRNAs (miRNAs) for breast cancer (BCa). However, the inconsistent results between studies have prevented the widespread usage of miRNAs in clinics. To systematically assess the potential diagnostic value of circulating miRNAs in BCa, we performed a comprehensive meta-analysis. Eligible studies were retrieved by searching electronic databases. The quality of the studies was assessed on the basis of quality assessment for stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 46 publications
3
12
0
Order By: Relevance
“…This was consistent with multiple studies which reported a high diagnostic value of serum miR-21 for BC [14,[43][44][45][46][47]. Some meta-analysis studies highlighted its role as a tumor biomarker, especially in the diagnosis of early-stage BC [43,44]. Others demonstrated a remarkable ability of circulating miR-21 levels to differentiate BC patients from healthy women with higher sensitivity and specificity than conventional serum biomarkers such as carbohydrate antigen 15-3 (CA15-3) and carcinoembryonic antigen (CEA), which exhibited low sensitivity and specificity, particularly in the context of early BC [45].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This was consistent with multiple studies which reported a high diagnostic value of serum miR-21 for BC [14,[43][44][45][46][47]. Some meta-analysis studies highlighted its role as a tumor biomarker, especially in the diagnosis of early-stage BC [43,44]. Others demonstrated a remarkable ability of circulating miR-21 levels to differentiate BC patients from healthy women with higher sensitivity and specificity than conventional serum biomarkers such as carbohydrate antigen 15-3 (CA15-3) and carcinoembryonic antigen (CEA), which exhibited low sensitivity and specificity, particularly in the context of early BC [45].…”
Section: Discussionsupporting
confidence: 93%
“…This was consistent with multiple studies which reported a high diagnostic value of serum miR-21 for BC [14,[43][44][45][46][47]. Some meta-analysis studies highlighted its role as a tumor biomarker, especially in the diagnosis of early-stage BC [43,44].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the detection of combined miRNAs showed a worse OS compared to the detection of single miRNAs. Hence, we proposed that the combined detection of miRNAs may serve as a stronger prediction methodPrevious meta-analyses confirmed that circulating miRNAs have a great potential in diagnosing human cancers [35,36], as the expression of circulating miRNAs significantly changes in cancer patients compared to healthy control. Circulating miRNAs may serve as ideal prognostic biomarkers, and the results of this meta-analysis support this hypothesis with a high HR value of 5.32 (95% CI: 2.37–11.93, P<0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…However, we anticipated that this subset of microRNAs would be diluted in serum and therefore would not be readily detected. To address this limitation, it may be important to use several microRNAs as biomarkers in order to strengthen the predictive power (Cui et al ., ). So far 16 microRNAs were identified as putative blood‐based markers of breast cancer in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…It is also important to note that these 16 microRNAs were identified and validated despite the existence of factors that are not directly related to cancer, yet can affect microRNA detection. For example, the collection and processing methods used for samples, the type of analytical platform employed, normalization of data, tumor stage, tumor grade, and/or patient ethnicity can all affect the microRNA profile of blood samples (Cui et al ., ). Thus, the 16 microRNAs identified and validated appear to be robust biomarkers and they should be further evaluated for their capacity to indicate the presence of breast cancer.…”
Section: Discussionmentioning
confidence: 97%